Solar Light-Driven Efficient Degradation of Organic Pollutants Mediated by S-Scheme MoS2@TiO2-Layered Structures - Shahid, Wajeehah; Idrees, Faryal; Zou, Ji-Jun; Choi, Jeong Ryeol; Pan, Lun (Nanomaterials (Basel, Switzerland), 2025)
This study focuses on achieving high photocatalytic activity using MoS2/TiO2 heterostructures (MOT). To this end, MoS2 and TiO2 were synthesized by employing hydrothermal synthesis techniques, and then MoS2/TiO2 heterostructures were synthesized by using 1:1, 1:2, 1:3, and 1:4 ratios of MoS2 and TiO2, respectively. While the structural and electronic changes for the 1:2 and 1:3 ratios were relatively minor, significant modifications in bandgaps and morphology were observed for the 1:1 and 1:4 ratios. Thus, this study presents a comparative analysis of the photocatalytic performance of the 1:1 (MOT11) and 1:4 (MOT14) heterostructures. The formation of these heterostructures was confirmed through Energy-Dispersive X-ray Spectroscopy (EDX) and Fourier Transform Infrared Spectroscopy (FTIR) analysis. Notably, the bandgaps of MOT11 and MOT14 were red-shifted to 1.66–1.25 eV and 1.01–1.68 eV, respectively, indicating improved visible-light absorption capabilities. The photocatalytic activity of MOT11 and MOT14 was evaluated through the degradation of Rhodamine B (RhB) under simulated solar irradiation. MOT11 demonstrated a high degradation efficiency of 98.9% within 60 min, while MOT14 achieved 98.21% degradation after 90 min of irradiation. The significance of this study lies in its demonstration that a facile synthesis route and a small proportion of MoS2 in the heterostructure can achieve excellent photocatalytic degradation performance under solar light. After MS-analysis, S-Scheme has been suggested, which has also been complimented by the scavenger tests. Additionally, the improved photocatalytic properties of MOT11 and MOT14 suggest their potential for future applications in hydrogen generation and water splitting, offering a pathway towards sustainable and clean energy production.